A modified drinking water quality index (DWQI) for assessing drinking source water quality in rural communities of Khuzestan Province, Iran. (June 2015) - Abtahi, Mehrnoosh; Golchinpour, Najmeh; Yaghmaeian, Kamyar; Rafiee, Mohammad; Jahangiri-rad, Mahsa; Keyani, Alidad; Saeedi, Reza
Graphical abstract: Highlights: An innovative DWQI for assessing drinking source water quality was introduced. The DWQI was applied to determine rural drinking source water quality of Khuzestan. The DWQI scores in the northern counties were higher than that in the southern ones. The provincial average score of the DWQI was 86 ± 9 (good designation). The DWQI was not particularly sensitive to any one parameter. Abstract: We reconsidered the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) to achieve an efficient drinking water quality index (DWQI) for assessment of drinking source water quality in rural communities of Khuzestan Province, Iran in 2009–2013. In contribution with a panel of water quality experts, the CCME WQI was mainly modified by four changes: (1 and 2) assigning weight factors for input parameters and index factors, (3) modifying excursion concept for carcinogens and bioaccumulative pollutants and (4) removing effect of unequal measurements of input parameters. The DWQI characterizes the drinking source water quality through comparing the measured values of input parameters with relevant benchmarks. The DWQI score (from 0 to 100) classifies the water quality in five categories as poor (0–54.9), marginal (55.0–69.9), fair (70.0–84.9), good (85.0–94.9) and excellent (95.0–100). Based on the DWQI, the temporal changes of the rural drinking source water quality were not significant; while the spatial variations of the water quality were considerable across the province, so the DWQI scores in the northern counties were higher than that in the southern ones. At the county level, the highest and lowest average scores of the DWQI (±standard deviation: SD) were observed in Izeh and Shadegan to be 90 ± 5 and 69 ± 10, respectively. Based on the DWQI, proportions of the drinking water sources with the excellent, good, fair, marginal and poor qualities were determined to be 6.7, 59.1, 26.2, 7.8 and 0.1%, respectively. Turbidity and Ryznar Index (RI) were introduced respectively as the health-based and esthetic parameters with the most violations (22.7 and 63.2%, respectively). The results of the case study and sensitivity analysis indicated that the DWQI is a simple, flexible, stable and reliable index and could be used as an effective tool to characterize drinking source water quality.